CAREER MYTHS FROM STUDENTS AND EDUCATORS PERSPECTIVE - Šmitiņa, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Drastic and structural changes in the labour market and organizational environment related to the Covid-19 pandemic, rapid technological development, general globalization trends, demographic deterioration and other economic changes signal the need to find new approaches to the classical career management paradigm. Several studies on occupational segregation show that various stereotypes and misconceptions affecting the choice of occupations for young people are still relevant, but changes in the working environment also determine changes in this context. The European Social Fund project “Career Support in General and Vocational Education Institutions” has made huge contributions to the improvement of the career guidance system in Latvia since 2016, developing and approbating career development support action plans, along with informative and methodological materials, as well as educating career counsellors and support specialists, thereby updating their approaches to career guidance and management. This study analysed the views of students and educational staff about current beliefs and stereotypes about career choices and management. Data from the 96 specialists and managers surveyed from different educational institutions reveal that educators have a strong belief in the importance of career stability. A majority believe that career choice is not always a guided process, although most support the involvement of career professionals. The importance of prestigious education and hard work, as well as success in one’s career, is emphasized. The 10th through 12th grade students were surveyed in 2019–2020 in Daugavpils, Dobele, Ogre and Riga general educational schools. In the opinions of these pupils, there is evidence of various stereotypes regarding the choice of profession, as well as the correspondence of career beliefs and convictions within the dynamics of modern working life.